PEMBERIAN ABU SEKAM PADI DAN FOSFAT ALAM PADA MEDIUM ULTISOL UNTUK MENINGKATKAN PERTUMBUHAN DAN HASIL PADI GOGO (Oryza sativa L.) - Fajri Ramadini; Nelvia Nelvia; Al Ichsan Amri (Jurnal Agroekoteknologi, 2019)
ABSTRACTRice as a staple food for most of Indonesia's population,their needs increase withincreasing population, conversely production decreases. One effort to meet theneeds of rice is by planting upland rice in dry land. Ultisol is the most extensivedry land in Indonesia. The yield of upland rice in Ultisol is very low, this iscaused by various problems including acid reaction, high Al saturation and Pfixation, availability of macro nutrients (N, P, K, Ca, Mg), low micro nutrients(Mo). Rice husk ash and natural phosphate can be used to increase pH andnutrient availability. The purpose of study was to study the effect of the interaction of rice husk ash and natural phosphate in increasing the growth andyield of upland rice (Oryza sativa L.) on Ultisol medium. The study was conducted at the Faculty of Agriculture greenhouse, University of Riau fromMarch to July 2019. The research was an experiment in the form of a 4x3 factorial using a completely randomized design. The first factor consists of four levels of rice husk ash (0.0; 1.5; 3.0; and 4.5 tons ha-1), the second factor of natural phosphate consists of 3 levels (0, 25 and 40 kg P2O5 ha-1), each repeated three times. The results showed the interaction between rice husk ash with a dose of 1.5 tons ha-1 and natural phosphate with a dose of 25 kg P2O5 ha-1 increased plant height, number of productive tillers, panicle length, number of paddy grains with pan, paddy grains and dry grain weight milled compared without rice husk ash and natural phosphate, each of these parameters tends to increase higher at the highest dose (4.5 tons ha-1 rice husk ash and 40 kg P2O5 ha-1 natural phosphate).